Cell proliferation suppressor RBR1 interacts with ARID1 to promote pollen mitosis via stabilizing DUO1 in Arabidopsis - Li, Lei (The New phytologist, 2025)
© 2025 The Author(s). New Phytologist © 2025 New Phytologist Foundation.